Financial Independence of Public Education Service Agencies: Integration of Value For Money Analysis and Per-11/PB/2021 from an Islamic Economic Perspective - Hasyim Bin Khomsi; Kamalul Iman Billah; Ayus Ahmad Yusuf (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to answer the main question regarding how the financial performance and level of independence of Public Bodies (BLU) at State Islamic Religious Higher Education Institutions, specifically UIN Siber Syekh Nurjati Cirebon, can be comprehensively evaluated through the integration of Value for Money (VfM), the PER-11/PB/2021 framework, and Islamic economic principles based on maqāṣid al-syarī‘ah. The research background is based on the urgency for Islamic higher education institutions to demonstrate fiscal governance that is accountable, efficient, and aligned with Sharia values. The novelty of the research lies in the development of an Islamic Value for Money (IVfM) evaluation model that combines quantitative indicators with Sharia parameters to produce a more holistic assessment. The research method uses quantitative-qualitative triangulation through analysis of audited financial statements for 2022–2024 and a normative study of maqāṣid. The results of the analysis show that the economic level is in the range of 86.09%–95.68%, the consistency efficiency level is above 100%, but the effectiveness fluctuates, with the highest RoA of 24.93%, liquidity is very strong (9.36–88.96x), and the level of independence has increased significantly to 88.23% in 2024. These results show BLU statistics and demonstrate the acoustics of governance with the principles of ḥifẓ al-maal, maslahah, and Istiqlal Al-Maal as the foundation of Islamic public finance. Penelitian ini bertujuan untuk menganalisis tentang kinerja keuangan dan tingkat independensi Badan Layanan Umum (PSA) pada Perguruan Tinggi Keagamaan Islam Negeri, dalam kasus ini adalah di UIN Siber Syekh Nurjati Cirebon, yang dapat dievaluasi secara komprehensif melalui integrasi pendekatan Value for Money (VfM), dalam kerangka PER-11/PB/2021, dan prinsip ekonomi syariah berdasarkan maqṣid al-syarī’ah. Penelitian ini dilatarbelakangi oleh urgensi perguruan tinggi Islam untuk menunjukkan tata kelola fiskal yang akuntabel, efisien, dan sejalan dengan nilai-nilai syariah. Penelitian ini menawarkan pengembangan model evaluasi Islamic Value for Money (IVfM) yang memadukan indikator kuantitatif dengan parameter Syariah untuk menghasilkan penilaian yang lebih holistik. Metode penelitian menggunakan triangulasi kuantitatif-kualitatif melalui analisis laporan keuangan auditan tahun 2022–2024 dan kajian normatif maqṣid. Hasil analisis menunjukkan bahwa tingkat perekonomian berada pada 86,09%–95,68%, tingkat efisiensi konsisten di atas 100%, namun efektivitas berfluktuasi dengan RoA tertinggi sebesar 24,93%, likuiditas sangat kuat (9,36–88,96x), dan peningkatan independensi yang signifikan hingga 88,23% pada tahun 2024. Hasil tersebut menggambarkan stabilitas fiskal BLU dan menunjukkan keselarasan tata kelola dengan prinsip-prinsip BLU. ḥifẓ al-maal, maslahah, dan Istiqlal Al-Maal sebagai landasan keuangan publik Islam.